Sunday
March 26, 2017

Post a New Question

Posted by on .

solve for c

A= -3(a + b - 1/3c)

  • math - ,

    Assuming you mean
    A= -3(a + b - (1/3)c)
    when parentheses are used correctly.

    Divide both sides by -3, and swap sides
    a+b-(1/3)c = -A/3
    -(1/3)c = -A/3-a-b

    Divide both sides by -(1/3)
    c = A+3a+3b

  • math - ,

    thank u

  • math :) - ,

    You're welcome!

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question